Growth of Myxovirus parainfluenza Type 3 in Organ Cultures of Guinea Pig Tissue - Craighead, J. E. (J Bacteriol, 1966)
Craighead, J. E. (Harvard Medical School, Boston, Mass.). Growth of Myxovirus parainfluenza type 3 in organ cultures of guinea pig tissue. J. Bacteriol. 92:751–761. 1966.—Organ cultures of adult guinea pig nasal mucosa, lung, and pleura were infected with Myxovirus parainfluenza type 3. Observations were made on the growth of virus at intervals after inoculation. An inoculum of 10(2.5) tissue culture infectious doses (tcid(50)) initiated infection in each of the tissues. Cultures of nasal mucosa yielded up to 10(6.0)tcid(50) per 6 hr for periods of as long as 2 weeks. Virus production was not affected by the “immune” status of the animal used as a source of tissue. Introduction of antiserum into the medium appeared to suppress virus release but failed to “cure” the infection. Interferon was not detected in fluids bathing the nasal mucosa. Cultured fragments of lung produced virus for 28 days after inoculation. As much as 10(5.0)tcid(50) per 6 hr was released by the tissue. Pleural mesothelial cells lining the diaphragm yielded up to 10(6.0)tcid(50) per 6 hr over a 14-day period. Histological sections showed that the tissues retained differentiated morphological features during maintenance in vitro. Cytological changes unequivocally associated with infection were not recognized. The techniques described give reproducible, quantitative results. Organ cultures are feasible for the study of virus growth and cytopathology in differentiated tissues. IMAGES: